Revitalisasi Sistem Pemasaran Perguruan Tinggi Islam di Era Globalisasi - Fauzi Fauzi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Globalization, with its entire power, has serious implication for Islamic higher education’s existence, primarily related with tight and open competition. This competition necessitated Islamic higher education to continuously revitalizing its education system and management, also revitalization and improvisation on its marketing system. Islamic higher educations must proactive and creative, not only waiting still. Therefore, marketing management that widely used at company domain, substantively its system and spirit must be implemented and adapted on Islamic higher education’s marketing system.